2020
DOI: 10.1186/s12711-020-0529-8
|View full text |Cite
|
Sign up to set email alerts
|

Beyond large-effect loci: large-scale GWAS reveals a mixed large-effect and polygenic architecture for age at maturity of Atlantic salmon

Abstract: Background Understanding genetic architecture is essential for determining how traits will change in response to evolutionary processes such as selection, genetic drift and/or gene flow. In Atlantic salmon, age at maturity is an important life history trait that affects factors such as survival, reproductive success, and growth. Furthermore, age at maturity can seriously impact aquaculture production. Therefore, characterizing the genetic architecture that underlies variation in age at maturity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
151
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(174 citation statements)
references
References 73 publications
9
151
5
Order By: Relevance
“… Sinclair-Waters et al (2020) recently characterized the mixed-effect architecture of age-at-maturity in Atlantic salmon, using an extensive genome-wide association study of 11,166 males from a single aquaculture strain, combined with high-density SNP arrays and pedigree information. Including the previously known large-effect vgll3 and six6 loci, they identified 120 genes contributing to age-at-maturity with various effect sizes.…”
Section: Eco-evolutionary Responses Hinge On Genetic and Genomic Archmentioning
confidence: 99%
See 1 more Smart Citation
“… Sinclair-Waters et al (2020) recently characterized the mixed-effect architecture of age-at-maturity in Atlantic salmon, using an extensive genome-wide association study of 11,166 males from a single aquaculture strain, combined with high-density SNP arrays and pedigree information. Including the previously known large-effect vgll3 and six6 loci, they identified 120 genes contributing to age-at-maturity with various effect sizes.…”
Section: Eco-evolutionary Responses Hinge On Genetic and Genomic Archmentioning
confidence: 99%
“…Unfortunately, such large-scale, high-throughput approaches as used for Atlantic salmon ( Sinclair-Waters et al 2020 ) are not feasible for most non-model species, which typically lack pedigree information and sufficient sample sizes and genomic resources, especially when they are of conservation concern. When the precise architecture is unknown, the genomic background (e.g., population or ecotype) in which a large-effect variant occurs can be considered as to whether it potentially influences expression of the focal variant for the trait of interest, but only if the variant is polymorphic within different genomic backgrounds.…”
Section: Eco-evolutionary Responses Hinge On Genetic and Genomic Archmentioning
confidence: 99%
“…This tradeoff might be particularly critical in semelparous species which experience a single reproductive episode before death. Age at maturity is often assumed to be influenced by many genes of small effect; however, recent studies have shown that the genomics of maturation age can be complex with mixed large-effect and polygenic architecture (Barson et al 2015, Sinclair-Waters et al 2020). While there are few cases where the genetic architecture of age at maturity is known, the genetic basis of age at maturation has important implications for how populations respond to selection (Kuparinen and Hutchings 2017) and how age diversity can be recovered if lost.…”
Section: Introductionmentioning
confidence: 99%
“…In Atlantic salmon, a single gene (VGLL3) explains 39% of the variation in age at maturity in European populations (Barson et al 2015) but does not appear to influence age at maturity in North American populations (Boulding et al 2019). In an aquacultural strain of Atlantic salmon, multiple genomic regions, including the VGLL3 gene, explained a total of 78% of the variation in age at maturity (Sinclair-Waters et al 2020). In Chinook salmon, the specific genes underlying variation in age at maturity are unknown but GWAS has identified SNPs associated with age at maturity on several autosomes (Micheletti and Narum 2018, Waters et al 2018) and male-specific sex chromosome haplotypes are associated with variation in size and age at maturity in male Chinook salmon from Alaska (McKinney et al 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, smaller fish are likely to have a higher probability of survival than the larger ones, and among them, those that can mature and reproduce early will be selected (Jorgensenet al , 2007;Jørgensen et al , 2009). Assuming that early maturation is heritable to some extent, this should result in life histories changing towards earlier reproduction at smaller sizes (Heathet al , 2002;Olsen et al , 2004;Ayllon et al , 2015;Sinclair-Waters et al , 2020).…”
Section: Introductionmentioning
confidence: 99%